(untitled) (Third Sector Social Economic Review, 2025)
The study aims to determine the effects of market multipliers, namely price/earnings ratio and market value/book value ratio, on the stock prices of banks. The study is based on quarterly bank data. The research period covers the years 2011-2024. During this period, panel data of 6 major commercial banks continuously traded on Borsa Istanbul in Türkiye were analyzed. In the study, FMOLS and DOLS estimation methods were used and finally the estimates were tested with the Robust least squares model. The same statistically significant findings were obtained in all estimation methods. Banks’ stock prices were accepted as dependent variable. Price/earnings ratio and market value/book value ratio were found to be independent variables that significantly affect the stock price. While the direction of the relationship was negative for the market value/book value ratio, a positive effect was observed for the price/earnings ratio. Market participants may have different interpretations of how multipliers will affect stock prices. According to the findings of the research, the negative effect of the price/earnings ratio indicates that this multiplier indicates undervaluation or overvaluation. In the case of undervaluation, when the multiplier is low, the price should increase to compensate for the undervaluation, or in the case of overvaluation, if the multiplier is high, the price should decrease to compensate. The positive effect of market value/book value indicates that this multiplier fully reflects expectations regarding the current situation of the company.